2021
DOI: 10.1111/ans.17446
|View full text |Cite
|
Sign up to set email alerts
|

Repeat two‐stage revision for knee prosthetic joint infection results in very high failure rates

Abstract: Introduction Two stage revision total knee arthroplasty (TKA) is the gold standard for treatment and eradication of knee prosthetic joint infections (PJI), but the literature is limited on the outcomes of repeat two‐stage TKA after PJI recurrence. This study presents the outcomes of repeat two‐stage revision TKA and investigates potential factors contributing to success or failure, aiming to assist counselling and decision‐making. Methods A retrospective study was undertaken investigating all two‐stage revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…In particular, the reinfection rate in this study was 17.8%, with a mean follow-up of 43 ± 17.1 months, also considering the high amount of already recurrent infections in the study population (62.2%). This appears to be a satisfactory result, as the failure rate of the two-stage procedure to treat chronic infection recurrence at the knee, even without bone resection, is reported to be up to over 70% [47][48][49]. The overall reinfection rate after DF MP in non-oncological settings was reported to be 7.9% in a recent review by Sambri et al [6].…”
Section: Discussionmentioning
confidence: 92%
“…In particular, the reinfection rate in this study was 17.8%, with a mean follow-up of 43 ± 17.1 months, also considering the high amount of already recurrent infections in the study population (62.2%). This appears to be a satisfactory result, as the failure rate of the two-stage procedure to treat chronic infection recurrence at the knee, even without bone resection, is reported to be up to over 70% [47][48][49]. The overall reinfection rate after DF MP in non-oncological settings was reported to be 7.9% in a recent review by Sambri et al [6].…”
Section: Discussionmentioning
confidence: 92%
“…[12][13][14][15] the available literature on repeat two-stage revisions for tKA infection is based on small cohorts or single centres reporting variable success rates and varying follow-up periods. 8,10,[16][17][18][19] Kim et al 20 have contended that culture outcome (positive vs negative) does not influence the outcome from two-stage revision, as measured by the likelihood of further surgical intervention. However, yang et al 21 demonstrated that prolonged postoperative microorganism directed antibiotics following two stage revision tKAs is associated with a significantly reduced likelihood of further infection.…”
Section: Introductionmentioning
confidence: 99%